Jerome Lejeune passed away 25 years ago - Soriano, Vicente (Hereditas, 2019)
During the past 60 years, modern genetics has steadily evolved from diagnostics to therapeutics. However, treatment of genetic disorders is still in its infancy, with the advent of genome editing as its greatest promise.
Keywords: trisomy 21; Jerome Lejeune; genetic diagnosis; gene editing; JCR; Scopus